Bentuk dan Makna Tata Rias Pengantin Tradisional Sari Agung Lumajang Jawa Timur - Maspiyah, Maspiyah; Lutfiati, Dewi; Kusstianti, Nia (Universitas Negeri Surabaya, 2019)
The purpose of this study is to identify the type and meaning of Sari Agung bridal make-up from Lumajang, East Java, which includes makeup and hairdo, and also clothing and accessories worn. This study is a descriptive study with qualitative approach. Data collection techniques using triangulation methods, which includes 1) interviews, 2) observation, and 3) documentation. Data sources in this study are senior bridal makeup artist in Lumajang, chairman of DPC Harpi Melati, and head of the Arts and Culture section of the Lumajang City Tourism Office. From the study results it is known that the Lamajang Sari Agung Bridal Makeup is a beautiful makeup, while the form of hair makeup is in the form of ˜ukel konde. Clothing and jewelry worn by the Lamajang Sari Agung bride; such as: jewelry made of silver; illustrates that Lumajang is a producer of silver crafts. The ˜dodot sinebab motives illustrate ˜pisang agung which is an icon of Lumajang. ˜Sekar manggis, ˜sulur pakis, etc describes natural wealth of Lumajang. Cinde fabric with empty palace motive describes the Lumajangs community belief that humans are born empty, carrying nothing.